Strategies for Municipal Bond Issuance in Financing Regional Development in the West Java Provincial Government 2023-2024 Case Study - Widyatmoko, Bondan; Nurdin, Nurliah; Sutrisno, Edy (Ilomata International Journal of Social Science, 2025)
The need for infrastructure development in West Java Province during 2018-2023 is IDR 861.9 trillion, while the local budget (APBD) capacity is only IDR 54.9 trillion, so there is a gap in financing needs of IDR 807 trillion. The West Java Provincial Government can use municipal bonds as an alternative for regional development financing, but this opportunity has yet to be utilized. This study aims to analyze the obstacles to issuing municipal bonds in West Java Province and establish issuance strategies. The bond success theory, according to Hardwood (2000), and the municipal bond aspect theory, according to Djaenuri (2012), are used to answer the research question. The methodologies used involve qualitative study. Data was obtained through document reviews and interviews. The results revealed that the obstacles are the commitment of the governor, project selections, regulation of the minister of finance regarding procedures for issuing municipal bonds that have yet to be published, and the readiness of the DMU. The strategies that can be implemented are commitment, project selection, regulatory, and DMU preparation strategies.Keywords: Municipal Bond, Infrastructure Financing, Creative Financing